Sarcopenia as a leading component of malignant cachexia syndrome - V. K. Lyadov; E. A. Bulanova; A. P. Seryakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
The aim of review. To analyze cumulative data of the global literature on skeletal musculature depletion or sarcopenia, in development of malignant cachexia syndrome, as well as diagnostics and clinical value of this state.Original points. Cachexia syndrome is one of the most frequent consequences of malignant disease. In the last years it was demonstrated, that sarcopenia plays the leading role in pathogenesis and progression of this state. Various procedures, including anthropometry, bioimpedance analysis, dual photon X-ray absorptiometry can be applied in diagnostics of sarcopenia. However, computer and magnetic-resonance tomography have the highest value for this goal. The article presents in detail data on clinical value of sarcopenia along with academical aspects of body composition analysis by radiological methods. Perspective trends of scientific studies in this area are proposed.Conclusion. Sarcopenia is the important component of malignant cachexia syndrome. Its investigation is perspective trend in clinical studies in oncology.